TOWARDS THE COHORT OF DISCIPLINED LEARNERS: HOW GLOBAL DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE CAN ACCELERATE SAFE SCHOOLS IN SOUTH AFRICA - Ngogi Emmanuel Mahaye (International Journal of Innovative Technologies in Social Science, 2025)
This study investigates the role of global digital technologies and artificial intelligence (AI) in accelerating safety and discipline in South African schools. The research focuses on how AI and digital tools can contribute to creating inclusive, safe, and secure learning environments in line with the principles of the global digital Compact and the Pact for the Future. Leveraging and drawing on Self-Determination Theory (SDT), this research explores how the effective management of teaching and learning, facilitated by digital technologies, can foster a cohort of disciplined learners. A systematic review methodology was employed to synthesise existing literature bias to global south on digital technology and AI’s role in school safety and discipline. Findings suggest that AI tools and digital platforms contribute to creating safer and more disciplined environments by offering personalized learning experiences, real-time feedback, and predictive analytics for behavioural management. The study highlights how integrating these technologies, alongside a focus on the innate psychological needs of learners, can drive positive outcomes in student behavior and academic performance. The findings also highlight the potential of digital education and AI in promoting safety and discipline, and academic excellence.